ANIMATION MEDIA DEVELOPMENT OF MULTIPLE REPRESENTATION BASED ON SCIENCE MATERIAL OF REACTION RATE DETERMINANT FACTORS - susanto susanto; nina kadaritna; noor fadiawati (Universitas Lampung, 2012)
Many Chemical concepts are abstract. Generally, chemical learning at this momen only in makroscopic and symbolic dimension, whereas submicroscopic often deserted. The research aim to develop animation media of multiple representation based on science material of reaction rate determinant factors. Method used is research and development (R D) according to Sugiyono (2008). Generally, research and development have three steps. There are step 1st) needs analysis, step 2nd) planning and development, and step 3th) evaluation the product. Results of this research is media of multiple representation based on science material of reaction rate determinant factors which have characteristic: 1) displaying science material of reaction rate determinant factors which be explained by multiple representation, 2) have parts consist of opening program title, foreword, instructional, competence standard, basic competence, indicators of product cognitive, indicators of process cognitive, science material of collision theory, science material of reaction rate determinant factors, literature, dan button for exit from the program, 3) have very high level of contents suitability that is 96.97 % according to teacher and also have high level of interesting that is 79.20% according students. Key words : animation media, multiple representation, reaction rate determinant factors.